A study on factors influence foreign language class anxiety among UiTM Kota Bharu students: A structural equation model / Noraim Ismail - Ismail, Noraim (Bachelor of Science (Hons.) Statistics, 2015)
This study aims to evaluate the communication apprehension, test anxiety and fear of negative evaluation factors towards anxiety level among UiTM Kota Bharu students. This study involved 250 of respondents by using stratified random sampling. Structural Equation Modeling (SEM) approach is used to analyse the inter-relationships among the multiple variables in a model. The result of independent samples t-test and Analysis of Variance (ANOVA) shows a significant different of the duration learning of foreign language only. Besides, the measurement model of these three factors shows a best fit (Root Mean Square of Error Approximation=0.068; Comparative Fit Index=0.953; Tucker-Lewis Index=0.946). The study suggested that the three-factor model was acceptable to be used to measure the level of anxiety among students because it is valid, reliable and simple